Diversity of Urine Bacteriology Practice in Ontario: An External Quality Assessment - Harold Richardson; Christine A Fleming; Andrew MR Mackenzie; The Microbiology Committee (Canadian Journal of Infectious Diseases)
OBJECTIVE: Assessment of urine bacteriology practice in Ontario regarding appropriateness of quantification and the accuracy and Système International d’Unités (SI) conformity in the reporting of results.